Artikel Review: Permen Inovatif Sebagai Solusi Kreatif Kurangi Rokok Dikalangan Remaja - Tarizza Puspa Anggrelia; Herta Meidya Nurhalita; Icasia Carolina Dewi; Yeka Khafidz Illa Rosyidah; Alfan Hermawan; Bella Fevi Aristia; Alfu Laili; Eka Putri Nurhidayah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The smoking habit among teenagers has become a serious health issue, with prevalence continually increasing. Smoking at a young age is associated with various health risks, including cancer, heart disease, and chronic obstructive pulmonary disease. One of the main contributing factors is peer influence and social environment. To reduce smoking habits, innovative approaches are needed, one of which is using innovative candies as an alternative to cigarettes. This study aims to analyze the potential of innovative candies in reducing smoking habits among teenagers. The method used is qualitative research with a literature review, collecting relevant scientific journal articles. The results indicate that candies such as Xylitol chewing gum, milk candy, cinnamon extract, and Vernonia cinerea extract can effectively reduce the frequency of smoking by providing a similar sensation without the negative effects of nicotine. Additionally, these candy products also have added benefits, such as improving oral and respiratory health. In conclusion, innovative candies can be a creative and effective solution to reduce smoking habits among teenagers, but further research is needed to assess their sustainability and long-term effects.